2014
DOI: 10.1155/2014/793040
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Nitric Oxide Synthase Gene Polymorphisms and the Risk of Hypertension in an Indian Population

Abstract: Genetic variants of eNOS gene play a significant role in the pathogenesis of hypertension. Many environmental factors have, also, been implicated in the aetiology of hypertension. We carried out an age-matched case-control study among adults. Hypertension was defined according to JNC-VII criteria and eNOS gene polymorphisms were determined by PCR and PCR followed by PCR-RFLP. eNOS intron 4 aa genotype (adjusted OR 6.81; 95% CI 2.29–20.25) and eNOS 894TT genotype (adjusted OR 7.84; 95% CI 2.57–23.96) were assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 42 publications
0
16
0
2
Order By: Relevance
“…For example, polymorphisms of the eNOS G894T gene have been linked to difficulties regulating heart rate and blood pressure. The presence of the T allele of this gene has been implicated in pathological conditions, including greater risk for hypertension (Shankarishan, Borah, Ahmed, & Mahanta, 2014). Conversely, homozygosity of the G allele is associated with lower diastolic blood pressure during a physical challenge (Nunes, Barroso, Pereira, Krieger, & Mansur, 2014).…”
Section: Genetic Influence On Heart Rate Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, polymorphisms of the eNOS G894T gene have been linked to difficulties regulating heart rate and blood pressure. The presence of the T allele of this gene has been implicated in pathological conditions, including greater risk for hypertension (Shankarishan, Borah, Ahmed, & Mahanta, 2014). Conversely, homozygosity of the G allele is associated with lower diastolic blood pressure during a physical challenge (Nunes, Barroso, Pereira, Krieger, & Mansur, 2014).…”
Section: Genetic Influence On Heart Rate Variabilitymentioning
confidence: 99%
“…Conversely, homozygosity of the G allele is associated with lower diastolic blood pressure during a physical challenge (Nunes, Barroso, Pereira, Krieger, & Mansur, 2014). It appears that the presence of the T allele alters the structure of eNOS and affects its activity by decreasing production of nitric oxide, which ultimately leads to higher blood pressure (Shankarishan et al, 2014).…”
Section: Genetic Influence On Heart Rate Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Зниження базаль-ної продукції NO може призводити до розвитку АГ, тромбозу та вазоспазму. Багатьма дослідженнями в різних популяціях показана асоціація розвитку АГ із поліморфізмом гена eNOS, зокрема із T786C [8,9,10,11]. З іншого боку, доведена потенційна роль NO в абдомінальній гемодинаміці при захворюваннях печінки.…”
Section: Conclusion the Development Of Hypertension In Patients Withunclassified
“…It has been found that Inhibition of eNOS elevates blood pressure in healthy humans and in mice disruption of eNOS gene leads to hypertension. 5 In hypertension, shear due to increased pressure can cause endothelial damage as the mechanisms of normal vascular remodeling is faulty due to impaired structural adaptation to elevated blood pressure and vasoconstriction. 6,7 When the vessel wall is damaged, sub endothelial matrix is exposed and platelets adhere to collagen with the help of α2β1 and glycoprotein(GP)V1 and to Von Williebrand factor (vWF) with the help of GPIbα and GPIIb/IIIa present on the platelet surface.…”
Section: Introductionmentioning
confidence: 99%